PENGEMBANGAN MODUL PEMBELAJARAN PERAWATAN WAJAH BERPIGMENTASI PADA CAPAIAN PEMBELAJARAN PERAWATAN WAJAH DENGAN TEKNOLOGI DI SMK 3 KEDIRI - Febrian Fauziah, Faza; Novia Restu Windayani; Nia Kusstianti; Octaverina Kecvara Pritasari (Program Studi Pendidikan Tata Rias, 2024)
This research seeks to create a technology-based pigmentation facial care learning module that is relevant to the implementation of technology in facial health at SMKN 3 Kediri. The ADDIE model is structured into five stages: analysis, design, development, implementation, and assessment. The use of pre- and post-test control group designs is common in this type of research. To obtain quantitative data, skills tests are used which are carried out on material experts, media experts, and other aptitude tests, knowledge tests, etc. Quantitative data is used to test the suitability of material experts, media experts, knowledge tests and skills tests. The results of data analysis by media experts obtained an average score of 4.80 (very decent). The results of analysis by material experts obtained an average score of 4.63 (very decent). Student learning outcomes are significantly different when using (advanced) learning modules compared to traditional methods, as shown by the knowledge competency learning outcomes. Students do not fall below the minimum proficiency level as a result of learning skills. This means that the modules developed can help improve learning outcomes in knowledge and skills competencies.